Tahsin Learning Methods in Improving Students' Al-Qur’an Reading Ability in Thawalib Boarding School, Padang - Rahman, Rina Aulia; Sulaiman, Sulaiman (Darul Yasin Al Sys, 2023)
Reading the Qur’an is a practice that is highly recommended and prioritized for Muslims, practicing it makes the reward double for the reader, but there are still Muslims who have not been able to read the Qur’an properly and correctly according to what was taught by Rasulullah SAW. This problem is based on the use of inappropriate methods at an early age. This study aims to analyze the tahsin learning method in improving the ability to read the Quran of students at the Thawalib Islamic Boarding School in Padang. This research uses the case study method. Sources of data were taken from five informants through in-depth interviews selected by purposive sampling technique, the informants were tahsin teachers and students at the Thawalib Islamic Boarding School in Padang. The results of the interviews were analyzed using the Miles and Huberman technique. The research findings show that: (i) Thawalib Padang Islamic Boarding School uses the talaqqi method to improve students' reading skills of the Quran, (ii) the implementation of learning through the planning, implementation, and evaluation stages, (iii) the ability of students at Thawalib Padang Islamic Boarding School is good and has been proven by the test results by the pesantren, (iv) there are also advantages, disadvantages, inhibiting and supporting factors in this tahsin learning.